Optimization of activated carbon production from corn cob using response surface methodology - He, Xiaoxue; Chen, Xuexue; Wang, Xinran; Jiang, Li (Frontiers in Environmental Science, 2023)
Waste management and valorization of waste is a major global issue. Low-cost and renewable adsorbent activated carbon (AC) from agriculture residues is a focus of worldwide concern. Microwave heating is an efficient technology for the production of AC. CCAC was synthesized from corn cob via microwave vacuum pyrolysis under vacuum ambient and the optimization process for maximized CCAC yield and its iodine number was developed using Response Surface Methodology (RSM). These regression models were having high Fischer test value & lower p-value which ensure its reliability and applicability. The optimized parameters obtained are 550.62W, 9.26min, -0.05Mpa and 1.7IR with responses of 37.57% yield and 933.38mg/g iodine number. The predicted results were validated and it was found that the experimental data varied only by 4.21% in yield and 4.02% in iodine number from the predicted values. The prepared adsorbent was characterized using Instrumental like FT-IR, BET and SEM. The pyrolysis approach produced CCAC containing regular and homogeneous porous structure with a specific surface area of up to 995.05m2/g, and total volume of 0.708 cm3/g.